2010
DOI: 10.1038/nrc2945
|View full text |Cite
|
Sign up to set email alerts
|

The renin–angiotensin system and cancer: old dog, new tricks

Abstract: For cancers to develop, sustain and spread, the appropriation of key homeostatic physiological systems that influence cell growth, migration and death, as well as inflammation and the expansion of vascular networks are required. There is accumulating molecular and in vivo evidence to indicate that the expression and actions of the renin-angiotensin system (RAS) influence malignancy and also predict that RAS inhibitors, which are currently used to treat hypertension and cardiovascular disease, might augment can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
515
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 447 publications
(540 citation statements)
references
References 185 publications
10
515
1
14
Order By: Relevance
“…5 It is likely that dysregulation of the normal physiological actions of the RAS in inflammation and angiogenesis might function to synergistically promote growth during malignancy. 8 Some reports using an AT1R antagonist and AT1R genedeficient (AT1a-/-) mice have shown that blocking AT1R signalling inhibited the growth of the following cells type: vascular endothelial, 19 prostate, 20 renal cell carcinoma 21 and pancreas. 22 In 2007, Imai and colleagues determined that AT1R-induced vascular endothelial growth factor a (VEGFa) signalling, in both host and tumour tissues, is one of the key regulators of tumour growth and tumour-associated angiogenesis.…”
Section: Inducing Angiogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…5 It is likely that dysregulation of the normal physiological actions of the RAS in inflammation and angiogenesis might function to synergistically promote growth during malignancy. 8 Some reports using an AT1R antagonist and AT1R genedeficient (AT1a-/-) mice have shown that blocking AT1R signalling inhibited the growth of the following cells type: vascular endothelial, 19 prostate, 20 renal cell carcinoma 21 and pancreas. 22 In 2007, Imai and colleagues determined that AT1R-induced vascular endothelial growth factor a (VEGFa) signalling, in both host and tumour tissues, is one of the key regulators of tumour growth and tumour-associated angiogenesis.…”
Section: Inducing Angiogenesismentioning
confidence: 99%
“…8 A hypoxic tumour environment, coupled with excessive accumulation of ROS, leads to oxidative stress, followed by increased protein modifications, cellular damage and death or increased growth factor signalling. 28 AngII induces the expression of p47phox and the production of the O2-radical through the activation of the AT1R in prostate cancer cells.…”
Section: Reprogramming Of Energy Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking p53 gene for example, the computed gene weights suggest that it acts as a core gene in pathways such as the p53 hypoxia signaling pathway ( Figure 1B) and p53 signaling pathway (with a high weight ranking top 1), and it participates but not dominates in pathways such as Huntington's disease pathway and cell cycle checkpoint pathway (ranking 72 and 102, respectively; Supplementary information, Table S1). Another example is the EGFR gene, which is suggested to be a more central gene in some pathways (such as AT1R pathway [27] and EGF pathway [28]) than others (such as calcium signaling pathway [29] and cytokine-cytokine receptor interaction [30]) (Supplementary information, Table S2). We have tested another functional association network named FunCoup [31], which produced similar gene weights in the pathways, with p53 hypoxia signaling pathway again taken as an example ( Figure 1C).…”
Section: Strategy Of Network-based Gene Weighting Within Pathwaysmentioning
confidence: 99%